Effect of acidity on growth rate and stroma formation of Monilia fructigena and M. polystroma isolates - Holb, I. J. (International Journal of Horticultural Science, 2004)
The effect of acidity (pH) ranges on the mycelial growth and stroma formation of Monilia fructigena Pers: Fr. and of M. polystroma van Leeuwen was determined on agar plates and apple fruits. Four isolates of each of the brown rot fungi and two apple cultivars, `James Grieve’ and ’Cox’s Orange Pippin’, were used for the study. For the agar plate study, a range of the initial pH was prepared from 2.5 to 6.5. The dishes were inoculated with a 4 mm plug of each isolate and incubated at 23 °C in darkness. The mycelial growth was measured after 1.5, 4, 7, 10 and 20 days of incubation. After a 30-day incubation, stroma formation was determined by image analysis and weighing of mature stroma. In the fruit experiment, both cultivars were inoculated with one isolate of M. fructigena and of M. polystroma. The pH changes were determined after 7, 14, 28 and 35 days of incubation in both healthy and inoculated fruits. The fastest mycelial growth was at pH 4.5 for M. polystroma and at pH 3.5 for M. fructigena. After a 30-day incubation, M. polystroma isolates produced twice or three times more stroma compared to M. fructigena isolates. For both brown rot fungi, the amount of mature stroma increased from pH 3.5 to 5.5, and then decreased at pH 6.5. Results of the.fruit experiment showed that healthy fruits were quite acidic (pH < 3.5), but pH rapidly increased in the inoculated fruits for both cultivars, reaching pH 4.6-5.4 depending on cultivar and fungus isolate. On both cultivars, the stroma developed at a significantly higher pH for M. polystroma than for M. fructigena. Biological and practical implications of the results are discussed.